Spectrum gamma ray borehole logging data of MeBo sediment core GeoB23213-1 - Tim Freudenthal (PANGAEA, 2020)
Logging was performed with the sea floor drill rig MARUM-MeBo200 in a borehole drilled with a 103 mm diameter bit. The 1460 Slimhole Memory SGR instrument developed by ANTARES Datasystems GmbH was used. A CsI(Na) crystal with outer diameter of 37 mm and 250 mm length is used as detector. The probe provides Natural Gamma Ray counts and analyses the spectrum for the concentrations of the natural gamma ray emitters potassium, thorium and uranium with an accuracy of about 10%. The probe was deployed in the memory mode with the logging string being inserted into the drill string and the sensors located below the drill bit. The measurement was conducted as upcast while the drill string was pulled back to the seafloor out of the borehole. The trip out speed was about 1 cm/s and the logging frequency was 0.5 Hz. Data processing was conducted using the Antares software GeoBase 6.22.1 assuming a constant bore hole diameter according the bit diameter.